CORRELATION OF CRIMINAL PROSECUTION AND PROTECTION OF THE RIGHTS AND FREEDOMS OF THE ACCUSED - Stoyko, Nikolay (State and Law, 2025)
The article discusses the relationship between criminal prosecution and protection of the rights and freedoms of the accused in the context of the typological characteristics of legal proceedings. Based on the comparative legal analysis, the author concludes that at present there is no explicit division of national criminal procedure systems into systems with the priority of substantive law over procedural law and systems with the priority of procedural law over substantive law.